The distribution of woodland caribou (Rangifer tarandus caribou) and moose (Alces alces) in the Fort St. James Region of Northern British Columbia, 1800-1950. - Santomauro, Domenico (Author); Johnson, Christopher (Thesis advisor); Fondahl, Gail (Thesis advisor); University of Northern British Columbia (Degree granting institution) (University of Northern British Columbia, 2009)
Throughout the 1800s and the 1900s, woodland caribou (Rangifer tarandus caribou) disappeared from the upper Nechako lowlands of the interior of British Columbia, and herds in the surrounding mountain ranges contracted. Conversely, moose (Alces alces) populations expanded during the 1900s and rapidly colonized former caribou habitat. Using historical-ecological methods of research and Geographic Information System (GIS) software, I documented caribou and moose historical distribution and abundance, and examined the causative mechanisms that led to caribou decline. I gathered historical information from four sources: 1) secondary literature 2) semi-structured interviews with aboriginal and non-aboriginal elders 3) journals of the Hudson's Bay Company of Fort St. James 4) other written primary sources. The findings of this study provide evidence of greater historical distribution and abundance of caribou, and confirm the value of Traditional Ecological Knowledge of First Nations (TEK) and of long-term historical perspectives for the study of ecological changes over time. --P. ii. The original print copy of this thesis may be available here: http://wizard.unbc.ca/record=b1659535